EFFECTIVENESS OF ACTIVATED BAMBOO CHARCOAL TO REDUCE TSS AND NEUTRALIZE PH OF WASTE WATER IN KOLAM PENGENDAPAN LUMPUR (KPL) OF PT. BUKIT ASAM PELABUHAN TARAHAN LAMPUNG - Oktaf Rina; Yatim Rahayu Widodo; Murni Fitria; Anggi Saputra; Rahmat Hidayat; Ajis Purnomo; Taty Silvia; Aang Haryadi; Syahdilla Anggiva Akhni (Sekolah Tinggi Pariwisata Mataram, 2023)
Water Treatment at PT Bukit Asam Pelabuhan Tarahan Lampung has carried out a waste treatment process in the Kolam Pengendapan Lumpur (KPL) which aims to purify or neutralize contaminated raw water into water that is categorized as clean according to quality standards. Bamboo charcoal was composed of carbon atoms which are known to have a high active surface area where it will increase along with the activation process. Activation of carbon can also be done by a combination of chemical and physical methods. In this study, the sorption capacity of activated bamboo charcoal was tested. ABT activity test on waste was carried out by batch method. In this method, ABT was put into an erlenmeyer flask containing liquid waste with a ratio of 1:50 (w/v). The mixture was then homogenized with a shaker at 150 rpm with a variation of soaking time of 10, 20, 30, 40, 50, and 60 minutes. The results concluded that the use of activated bamboo charcoal can reduce TSS to 15 mg/L and pH to 7.5. The use of activated bamboo charcoal can be recommended as a replacement component for alum in sewage treatment